Biology e-magazine integrated on wahdatul ‘ulum: Learning media on reproductive system material - Melina Sari; Miza Nina Adlini (BIO-INOVED : Jurnal Biologi-Inovasi Pendidikan, 2024)
Biology learning media that are interesting, easy to use, and effective in improving the quality of students and integrated with Islamic values such as wahdatul ‘ulum need to be developed. Wahdatul ‘ulum is one of the main concepts in the philosophy of science at the Universitas Islam Negeri Sumatera Utara (UINSU). This study aims to analyze the validity, practicality, and effectiveness of the integrated biology e-magazine on the wahdatul ‘ulum paradigm developed on reproductive system material. The type of research used is research and development (RnD) with the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The instruments used in this research are interview sheets, needs analysis questionnaires of biology teachers and students, validation sheets of material experts, media experts, and wahdatul ‘ulum experts, response questionnaires of biology teachers and students, and multiple-choice question tests. The results showed that the validity of e-magazines from media experts obtained a percentage of 94.70% (very valid), material experts obtained a percentage of 95.83% (very valid), and wahdatul ‘ulum experts obtained a percentage of 87.50% (very valid). The practicality of e-magazines is that the response of biology teachers obtained a percentage of 92.50% (very practical), and the response of students obtained a percentage of 91.06% (very practical). The effectiveness of e-magazines is known from N-Gain results of 0.72 (effective). The advantages of biology e-magazines on reproductive system material developed because it is integrated with the wahdatul ‘ulum paradigm, easy to understand, attractive in design, and able to improve learning outcomes, although in the aspect of motivating students to enthusiasm for learning has not reached good criteria. Further research is needed to achieve a broader goal of shaping the positive character of students.Abstrak. Media belajar biologi yang menarih, mudah digunakan, dan efektif untuk meningkatkan kualitas peserta didik serta terintegrasi dengan nilai-nilai keislaman seperti wahdatul ‘ulum perlu dikembangkan. Wahdatul ‘ulum adalah salah satu konsep utama dalam filsafat ilmu di Universitas Islam Negeri Sumatera Utara (UINSU). Penelitian ini bertujuan untuk menganalisis kevalidan, kepraktisan dan keefektifan e-majalah biologi terintegrasi paradigma wahdatul ‘ulum yang dikembangkan pada materi sistem reproduksi. Jenis penelitian yang digunakan adalah penelitian dan pengembangan atau Research and Development (RnD) dengan model ADDIE (Analysis, Design, Development, Implementation, Evaluation). Instrumen yang digunakan pada penelitian ini adalah berupa lembar wawancara, angket analisis kebutuhan guru biologi dan peserta didik, lembar validasi ahli materi, ahli media, dan ahli wahdatul ‘ulum, angket respon guru biologi dan peserta didik, serta tes soal pilihan ganda. Hasil penelitian menunjukkan bahwa kevalidan e-majalah dari ahli media diperoleh persentase sebesar 94,70% (sangat valid), dari ahli materi diperoleh persentase sebesar 95,83% (sangat valid), dan dari ahli wahdatul ‘ulum diperoleh persentase sebesar 87,50% (sangat valid). Kepraktisan e-majalah dari respon guru biologi diperoleh persentase sebesar 92,50% (sangat praktis) dan dari respon peserta didik diperoleh persentase sebesar 91,06% (sangat praktis). Kefektifan e-majalah diketahui dari hasil N-Gain 0,72 (efektif). Kelebihan dari e-majalah biologi materi sistem reproduksi yang dikembangkan karena terintegrasi dengan paradigma wahdatul ‘ulum, mudah dipahami, desain menarik, dan mampu meningkatkan hasil belajar, meskipun pada aspek memotivasi peserta didik untuk semangat belajar belum mencapai kriteria baik. Penelitian lebih lanjut diperlukan untuk mencapai tujuan yang lebih luas yaitu membentuk karakter positif peserta didik.